2017
DOI: 10.1038/ncomms15616
|View full text |Cite
|
Sign up to set email alerts
|

INO80 exchanges H2A.Z for H2A by translocating on DNA proximal to histone dimers

Abstract: ATP-dependent chromatin remodellers modulate nucleosome dynamics by mobilizing or disassembling nucleosomes, as well as altering nucleosome composition. These chromatin remodellers generally function by translocating along nucleosomal DNA at the H3–H4 interface of nucleosomes. Here we show that, unlike other remodellers, INO80 translocates along DNA at the H2A–H2B interface of nucleosomes and persistently displaces DNA from the surface of H2A–H2B. DNA translocation and DNA torsional strain created near the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
135
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(164 citation statements)
references
References 75 publications
20
135
1
Order By: Relevance
“…The ATP-dependent nucleosome remodelling activity of INO80 has been proposed to preferentially target and promote eviction of the histone variant H2A.Z from nucleosomes (Brahma et al, 2017;Eustermann et al, 2018;Papamichos-Chronakis et al, 2011). In agreement with a role for H2A.Z in RNA quality control and non-poly(A) transcription termination (Muniz et al, 2017;Wagner et al, 2007;Zofall et al, 2009), our results suggest that INO80 promotes recruitment of Nab2 to chromatin by regulating its interaction with H2A.Z ( Figure 6).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The ATP-dependent nucleosome remodelling activity of INO80 has been proposed to preferentially target and promote eviction of the histone variant H2A.Z from nucleosomes (Brahma et al, 2017;Eustermann et al, 2018;Papamichos-Chronakis et al, 2011). In agreement with a role for H2A.Z in RNA quality control and non-poly(A) transcription termination (Muniz et al, 2017;Wagner et al, 2007;Zofall et al, 2009), our results suggest that INO80 promotes recruitment of Nab2 to chromatin by regulating its interaction with H2A.Z ( Figure 6).…”
Section: Discussionsupporting
confidence: 86%
“…We next sought to gain insight into how chromatin regulation by INO80 promotes recruitment of Nab2 to chromatin. INO80 preferentially remodels nucleosomes containing the histone variant H2A.Z, controlling the dynamics of H2A.Z enrichment on chromatin (Brahma et al, 2017;Eustermann et al, 2018;Papamichos-Chronakis et al, 2011;Yen et al, 2013). Previous observations in D. melanogaster and S. pombe have suggested a role for H2A.Z in RNA quality control and non-poly(A) transcription termination (Muniz et al, 2017;Wagner et al, 2007;Zofall et al, 2009).…”
Section: Defective Nns-dependent Transcription Termination In the Absmentioning
confidence: 97%
“…The reason for this instability is unclear, but was observed with two different positioning sequences. While present evidence suggests that Chd1 shifts nucleosomes when at SHL2 (Nodelman et al, 2017), two recent studies have shown that remodeler ATPases can also engage with the outer gyre of DNA: the isolated SWI/SNF ATPase, in a cryoEM study, was shown to bind SHL6 as well as SHL2 (Liu et al, 2017), and yeast INO80 was shown to reposition nucleosomes by translocating on DNA around SHL5 (Brahma et al, 2017). For Chd1, reversal of DNA movement may therefore result from translocation of the ATPase at the SHL2 site on the opposite side of the nucleosome (Figure 3G, model 1), or by reorienting to SHL5 or SHL6 on the opposite gyre, which is close to the first SHL2 site (Figure 3G, model 2).…”
Section: Discussionmentioning
confidence: 66%
“…Previously, it had been shown that INO80 remodeling on all tailless nucleosomes is faster than for wild-type nucleosome [45] and that initiation of remodeling is functionally different from the continued remodeling reaction by INO80 [49]. More precisely, nicked nucleosome constructs have been reported to have a considerable effect on initiation of remodeling by INO80, but only have marginal effects on continued remodeling [49]. Based on these results and the data presented here, we conclude that the histone tails are a major regulatory barrier for INO80 nucleosome invasion.…”
Section: Discussionmentioning
confidence: 99%